Last Days in Fiume - Takács, Zsuzsanna Mária (Acta Scientiarum Socialium, 2012)
Last Days in Fiume. Fiume, today’s Rijeka, lives in many ways in the Hungarian historical memory. During the past centuries a picture developed that is connected to the „Hungarian” port. However, it is questionable how Fiume and the education there were „Hungarian”, what the everyday life, the schooling were in a community where most of the inhabitants spoke not the official language of the state, and belonged to another culture. On the basis of three totally different primary written sources, the study attempts to introduce how differently those people saw Fiume and the last „Hungarian” months that lived as teachers, students and at the same time as members of different nationalities for longer or shorter periods in the seaside town. The centre of our research was the sources from the 1910s. Following the comparative analysis of works connected to Fiume by Agliceriu Remus and Samu Szabó, school directors in Fiume and Olga Koós, teacher, we can get a picture different from the general about the town before 1918. By analysing their works we got an insight into an interesting, but so far unknown part of Fiume’s school history.